KONSTRUKSI TAFSIR ILMI KEMENAG RI-LIPI: Melacak Unsur Kepentingan Pemerintah dalam Tafsir - Barmawi, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This article aims to explore ”scientific exegesis”of ministry of religious affairs of Indonesia. As we know the scientific exegesis is one of the approaches in interpreting the Qur’an which appeared since the middle century. This will try to explore the epistemology of that exegesis and the interest of government in process of writing the exegesis. It will focus in three themes namely ocean, food and a drink, and time. This concludes that first this exegesis is a part of the thematic method. Second, according to validity aspect, this exegesis agrees with the correspondence and pragmatism aspect, but not in coherence aspect. Third, this exegesis is an effort to help the policy of government.